Two Odysseys of ’Americanization’: Dreiser’s An American Tragedy and Grove’s A Search for America - Gammel, Irene (Studies in Canadian Literature, 1992)
Theodore Dreiser’s An American Tragedy and Frederick Philip Grove’s A Search for America are similar in their focus on the metaphor of America. Juxtaposing the two works gives insight into significant differences in Canadian and American conceptions of personal and national identity and valuations of the margins. Both protagonists, Dreiser’s Clyde Griffiths and Grove’s Phil Branden, suffer from their position as social outsiders and develop strategies to deal with their marginalization. The Canadian traveller distinguishes himself from his American counterpart through his self-conscious linguistic flexibility. Branden survives, not because he creates a name or well-defined identity for himself, but because he eludes the notion of a fixed identity in his journey towards self-creation. Griffiths’s yearning to merge with the society that excludes him means that the only self he has is the one he will become; his language is emptied of meaning until he vanishes like a "nobody." In both novels, metaphors of self-creation are interwoven with metaphors of national identity. Dreiser’s ironic tragedy dramatizes the ultimate expulsion of the scapegoat; Grove’s ironic comedy-romance ends with the protagonist’s overt reconciliation with North American society.